Review of Gum Arabic Production, Sudan - M. A. Eisa; Hanan M. Elhadi (Cutting Edge Research in Biology Vol. 1, 2022)
In the current paper, the production of gum in Sudan was examined historically. According to the FAO/WHO Joint Expert Committee on Food Additives, gum Arabic is an exudate of Acacia senegal. Acacia senegal is also known as “Kordofan gum” denoting the region as a primary production area for this internationally-renowned species of gum arabic. Sudan is the world’s largest producer and exporter, contributing 80 to 90% of the world’s supply of this commodity. Acacia senegal trees help improve soil health and restrict climate change as well as the expansion of deserts in arid and semi-arid regions. Gum Arabic is a mixture of potassium, magnesium and calcium salts of polysaccharide acid and is easily soluble in water. During the last 30 years, production in Sudan has shown alarming signs of overall decline as well as a significant year-to-year variation. Furthermore, during the 1990s, world exports began to pick up momentum again, but exports from Sudan almost remained the same, due to stagnant production in Sudan as well as increasing competition from other exporters. The objectives aimed to review gum arabic production, stability, and fluctuation as well as the ongoing research finding in the last years.